RETROSPECTIVE: Dark Silicon and the End of Multicore Scaling - Esmaeilzadeh, Hadi; Blem, Emily; St. Amant, Renee; Sankaralingam, Karthikeyan; Burger, Doug (ISCA@50 25-Year Retrospective: 1996-2020, 2023)
An invited author retrospective on "Dark Silicon and the End of Multicore Scaling" originally published at ISCA 2014. Included in the ISCA@50 25-Year Retrospective: 1996-2020.